Rural Development Initiative Through Nature-Based Tourism Development: Challenges and Opportunities - Muslih Faozanudin; Lilis Sri Sulistiani (Public Administration, Faculty of Politics and Social Science, Universitas Jenderal Soedirman, Indonesia, 2026)
The development of rural areas based on the nature-based tourism in the mountainous area of ​​Kendeng, Somagedhe District is a strategic for the local community. The natural potential with their exotic scenery in the area is possible to be developed as an alternative to rural tourism destinations. Village development by improving natural tourism in this village is intended to support the economic growth of the local community. Attempts to realize this idea have also been carried out in several ways, such as coordinating with all stakeholders, community leaders and consulting with tourism experts. Development efforts have begun, there are still facing several challenges including: there is still a lack of skilled personnel to manage tourism, there is lack commitment among stakeholders including from local village government leaders, low quality of tourism infrastructure such as access roads and parking areas. Behind these limitations, there are actually very open opportunities for the Kendeng mountain region as an exotic and interesting tourist destination to be developed, especially for the economic development of the local community.